0502 Safety, Tolerability, and Efficacy of a Novel, Highly Potent and Selective Partial Agonist for Nociceptin/Orphanin-FQ Peptide (NOP) Receptors in Patients with Insomnia Disorder. (27th May 2020) - Zhou, M; Harris, S; Kapil, R; Cipriano, A; He, E; Shet, M; Fukumura, K; Matsuo, Y; Uehira, M; Zammit, G
Abstract: Introduction: V117957 is a recently described investigational oral, potent, and selective nociceptin/orphanin-FQ peptide (NOP) receptor partial agonist which was previously evaluated in ~200 healthy subjects. Its satisfactory safety/tolerability profile has been established with the top doses at 30mg following a single oral administration and 10mg once daily for 2 weeks. V117957 demonstrated favorable drug-like properties for insomnia treatment, including oral bioavailability, fast absorption, and rapid elimination. Methods: A total of 52 patients with insomnia disorder have been evaluated in two separate randomized, double-blind, crossover, placebo-controlled sleep studies. Insomnia disorder was confirmed by screening polysomnography (PSG). All subjects received orally, for two consecutive nights, either V117957 10mg or placebo in Study #1 or 0.5, 1, 3, 6mg or placebo in Study #2. Efficacy was measured via PSG for the primary endpoint of sleep efficiency (SE) and secondary endpoints of sleep onset (latency to persistent sleep [LPS]) and maintenance (wakefulness after sleep onset [WASO]). Efficacy also was measured by patient diary (subjective sleep latency [sSL], subjective total sleep time [sTST], sWASO). Pharmacodynamics (PD) on next-day residual effects were also measured, including cognitive, psychomotor and mood effects. Results: V117957 showed statistically significant greater sleep efficiency and less WASO in a dose-dependent manner (0.5-10 mg) and a statistically significant reduction in LPS at 10mg, as compared to placebo. V117957 at 0.5mg and 1mg exhibited next-day residual effects similar to placebo. At doses of 3mg or higher, V117957 showed dose-dependent next-day residual effects. V117957 was safe and well-tolerated across all doses tested with no serious adverse events, with somnolence being the most frequent treatment-emergent adverse event. No concerning laboratory findings and no clinically significant findings on vital signs and electrocardiograms have been attributed to V117957 in these subjects. Conclusion: V117957 was safe and well-tolerated in patients with insomnia disorder. These results demonstrated that NOP receptors represent a novel mechanistic treatment for insomnia disorder and support continued evaluation of V117957. Support: Funded by Shionogi and Imbrium Therapeutics, a subsidiary of Purdue Pharma L.P.